A Tandem Ring Opening/Closure Reaction in A BF3‐Mediated Rearrangement of Spirooxindoles. Issue 24 (16th October 2017) - Guo, Xuliang; Xing, Qingyu; Lei, Kunhua; Zhang‐Negrerie, Daisy; Du, Yunfei; Zhao, Kang
Abstract: Treatment of the readily accessible spiro‐cyclohexadienones from the PhI(OCOCF3 )2 ‐mediated spiro‐cyclization of N‐substituted benzanilides, with BF3 ⋅Et2 O initiates a tandem ring opening/closure reaction leading to the formation of the biologically interesting 8‐hydroxy‐phenanthridin‐6(5 H )‐one compounds. This unique rearrangement pattern involves the 'migration' of the electron‐deficient N ‐methyl carbamoyl moiety rather than the electron‐rich aryl group as observed and reported previously in all other similar transformations. Abstract :